Proceedings of the 2016 ACM International Joint Conference on Pervasive and Ubiquitous Computing: Adjunct 2016
DOI: 10.1145/2968219.2968317
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mood changes on application selection

Abstract: Users of quantified self applications habitually log and track personal information, such as mood. Attempts to automate the procedure of logging mood have been made, but applications themselves rarely provide insights into the user's mental well-being. In this paper we explore data from two small scale studies related to mobile device usage and mood tracking. We analyse associations between user's mood throughout the day and the use of smartphone applications from different categories. Our analysis provides in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
(6 reference statements)
1
5
0
Order By: Relevance
“…From four previously published studies [10,14,35,37], we aggregate a dataset of 347,576 smartphone screen entries, from 445 unique users between February 2014 and May 2016, which we then transform into 120277 unique usage sessions. Each session has an associated session length (M = 229.34 seconds), and the daily session count (M = 60.08) for that user on that particular day.…”
Section: Comparison To Smartphone Datasetmentioning
confidence: 99%
“…From four previously published studies [10,14,35,37], we aggregate a dataset of 347,576 smartphone screen entries, from 445 unique users between February 2014 and May 2016, which we then transform into 120277 unique usage sessions. Each session has an associated session length (M = 229.34 seconds), and the daily session count (M = 60.08) for that user on that particular day.…”
Section: Comparison To Smartphone Datasetmentioning
confidence: 99%
“…Emotion-sensing has long been in the focus of Human-Computer Interaction (HCI) and ubicomp research -even giving rise to a new research field: Affective Computing [18]. Recent changes in consumer behavior and technological progress have created new opportunities for research and for the application of emotion detection technology in everyday life, e.g., emotion detection from smartphone usage behavior [19,20,24]. But, critical voices questioning the actual ability to detection emotion have become more prominent.…”
Section: Objectives and Impactmentioning
confidence: 99%
“…There have also been several attempts to derive users' emotional state from application use data. In a study by Visuri et al [99], the authors map users' affective state to applications use. They found that when experiencing positive affect, the users tend to use Media, Games, Maps and Travel applications.…”
Section: Application Use Behaviourmentioning
confidence: 99%